(untitled) (Medico Legal Update, 2021)
WHO categorizes driver distraction like mobile usage as an important risk factor for road crash injuries, as driver’s reaction time increases causing difficulty in: maintaining correct positions in their lanes, maintaining appropriate speeds and judging safe gaps in traffic. Descriptive study with objective of assessing knowledge, attitude and practices regarding mobile usage while driving amongst medical and engineering students aged 18-21 years was carried out using proforma after taking consent. During driving, most of medical (61%, 79%) & engineering (60%, 69%) students called & received calls; 55% & 60% knew it is distracted driving & only 43% & 46% always considered it as punishable respectively. 42% & 30% read and 34% & 18% texted message; 53% & 26% used social media (WhatsApp, Facebook etc); most viewed maps/directions on their phone and felt that pedestrians using mobile are prone for accidents. Although 87% & 88% would advice others, only 52% & 55% would restrain mobile usage during driving respectively. This study suggest for improving on-ground situation through formal education to bring about moral responsibility amongst youth and propose automatic electronic system in vehicles for early detection of this globally identified risk factor